"\\frac{d^{2}y}{dx^2}-6\\frac{dy}{dx}+9y=1+x+x^{2}"
P(s)=s2-6s+9
=(s-3)2
Since we have two identical roots,the homogeneous solution will have the form ;
yh=C1e3x + C2xe3x
yp=Ax2+Bx+C
y'p=2Ax+B
y''p=2A
9Ax2+(9B-12A)x+(2A-6B+9C)=x2+x+1
9A=1 "\\implies" A="\\frac{1}{9}"
9B-12A=1 "\\implies B=\\frac{7}{27}"
2A-6B+9C=1"\\implies C=\\frac{7}{27}"
So yp="\\frac{1}{9}x^{2}+\\frac{7}{27}x+\\frac{7}{27}"
"\\therefore" The general solution is:
"y=C_1e^{3x}+C_2xe^{3x}+\\frac{1}{9}x^{2}+\\frac{7}{27}x+\\frac{7}{27}"
Comments
Leave a comment